Analysis of Information Technology Utilization and Internal Control Systems in Efforts to Enhance the Reliability of Bombana Regency Government Financial Reports - Surianto Ilham; Muh. Sukran; Andi Iswan (Journal of Creative Power and Ambition (JCPA), 2026)
This study is motivated by the importance of public accountability achieved through reliable local government financial reporting. The research aims to analyze the utilization of Information Technology (IT) and the Internal Control System (ICS) in enhancing the reliability of financial reports within the Bombana Regency Government. A descriptive qualitative method was employed, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that IT utilization has been implemented through the SIPD RI application and human resource development, although challenges regarding hardware infrastructure and network stability persist. The application of the five ICS components has proceeded effectively, particularly regarding the control environment and routine monitoring to mitigate fraud risks. An analysis of financial reports from the 2020–2024 period demonstrates the positive contribution of IT and ICS to report reliability, despite continued fluctuations in Locally-Generated Revenue (PAD) and a high reliance on transfer funds. In conclusion, synergy between strengthening technological infrastructure and managing system risks is essential to ensure the accuracy and timeliness of future financial reporting.